2015
DOI: 10.1145/2817830
|View full text |Cite
|
Sign up to set email alerts
|

Coalescing-Branching Random Walks on Graphs

Abstract: We study a distributed randomized information propagation mechanism in networks we call the coalescingbranching random walk (cobra walk, for short). A cobra walk is a generalization of the well-studied "standard" random walk, and is useful in modeling and understanding the Susceptible-Infected-Susceptible (SIS)-type of epidemic processes in networks. It can also be helpful in performing lightweight information dissemination in resource-constrained networks. A cobra walk is parameterized by a branching factor k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 53 publications
(54 reference statements)
6
40
0
Order By: Relevance
“…• We show that the cover time for the 2-cobra walk for a d-regular graph with conductance φG is O(φ −2 G log 2 n). This generalizes a similar result in [13] for expander graphs with sufficiently high expansion. Our new result holds for any d-regular graph, and expresses the bound as a function of the conductance.…”
Section: Our Results and Techniquessupporting
confidence: 88%
See 4 more Smart Citations
“…• We show that the cover time for the 2-cobra walk for a d-regular graph with conductance φG is O(φ −2 G log 2 n). This generalizes a similar result in [13] for expander graphs with sufficiently high expansion. Our new result holds for any d-regular graph, and expresses the bound as a function of the conductance.…”
Section: Our Results and Techniquessupporting
confidence: 88%
“…We show that the cover time for the d-dimensional grid using a 2-cobra walk [0, n] d is O(n), where the order notation hides constant factors and other terms that depend on d; indeed, we show all vertices are covered in O(n) steps with high probability. Previous work has shown that the cover time is O(npolylog(n)) [13]. 1 Our result is clearly tight in its dependence on n. Moreover, it shows that in some circumstances one can avoid using tools such as Matthews' Theorem, which had been used previously in this setting [13], and necessarily adds in an additional logarithmic factor in the number of vertices over the hitting time.…”
Section: Tight Results For Gridssupporting
confidence: 56%
See 3 more Smart Citations